OPTIMALISASI STRATEGI PEMANASAN KOMBINASI PELEPASAN MIOFASIAL DAN PEREGANGAN DINAMIS DALAM SEPAK BOLA PERGURUAN TINGGI - M. Said Zainuddin; Ahmad Zakaria; Fatoni Fatoni (YLPK Mahardhika, 2026)
Optimizing pre-exercise routines is critical for enhancing athletic performance in higher education sports programs. This study investigated the acute effects of three different warm-up protocols—self-myofascial release via foam rolling (SMR), dynamic stretching (DS), and a combined SMR+DS protocol—on functional performance parameters in university soccer players. Using a randomized crossover experimental design, 60 male sports science students from Universitas Negeri Makassar underwent three testing sessions separated by a 48-hour washout period from February to April. Performance metrics evaluated included flexibility (sit-and-reach), explosive power (vertical jump), speed (20-meter sprint), and agility (Illinois agility test). Repeated measures ANOVA revealed that the combined SMR+DS protocol yielded the highest significant improvements in agility (p < 0.05) and speed (p < 0.05) compared to standalone interventions. While SMR significantly enhanced flexibility without compromising vertical jump height, the integration of DS following myofascial release provided a synergetic potentiation effect on neuromuscular performance. These findings demonstrate that a sequential combination of SMR and dynamic stretching optimizes acute functional performance. Consequently, coaches and educators should integrate combined warm-up strategies into higher education soccer curricula to maximize explosive power and mechanical efficiency during high-intensity intermittent activities.